TINJAUAN KUAT TEKAN BATA RINGAN MENGGUNAKAN BAHAN TAMBAH FOAMING AGENT - Arita, Deri; Kurniawandy, Alex; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lightweight bricks could be used as the substitute of conventional bricks for building wall materials. Lightweight brick has a weights beetween 600 to 1800 kg/m3. In this research, lightweight bricks were made by trial and errors made by adding combination of 0.3%, 0.6%, 0.9%, 1.2% and 1.5% of foam agent by cellular lighweight concrete (CLC) method. The optimum compresive strength was gain at 0.9% of foam agent. CLC lightweight brick is the type of bricks which is constructed by adding air bubbles/foam agent to mortar mixture. It is necessary for the air bubbles to retain their shapes during the curing process of the mortar without triggering chemical reaction. An airlock was in a mixture of mortar structure of the cells that produce material, which contains the cavity the air with the size of the between 0,1 to 1,0 mm thick and spread uneven so that makes the nature of concrete better to prevent heat and more voice The curing process was performed by storing the samples indoor, in which the room temperatur varies over time. The sample size was 60x20x7.5 cm, made to investigate the impact of foaming agent to the compressive strength of the lightweight bricks. The experiment method was carried out based on SNI 03-6825-2002. As a result, the compressive strength was 0.49 MPa at 7 days, 0.23 MPa at 14 days, and 0.67 MPa at 28 days. In addition, according to the furnace tests, the lightweight bricks resist for heat temperature of 500ºC. Also, The acoustic test results also shows that the lightweight bricks absorb sound by 3%.Keywords : brick light, foam agent, strong press, acoustic monitoring, furnace